Peran Budaya Perusahaan Terhadap Usaha Penciptaan Kinerja Karyawan - Zhiella Sabrina Darwis; Syafiq Basri Assegaff (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
This study aims to determine the role of organizational culture in improving employee performance at PT Telekomunikasi Indonesia, Tbk, especially senior employees at the Human Capital Strategic Management division. PT Telekomunikasi Indonesia, Tbk create a team named Culture Agent to communicate about the transformation of the culture in company. In the results of the study it can be concluded that changes in organizational culture can improve employee performance in completing the given task. And also can eliminate the seniority attitude that exists in PT Telekomunikasi Indonesia, Tbk.